Designing Learning Trajectory on Ratio and Proportion through PMRI with the Indonesian Traditional Food Context - Lucy Asri Purwasi; Zulkardi; Ratu Ilma Indra Putri; Ely Susanti (Journal of Honai Math, 2025)
Mastery of the concepts of ratio and proportion is essential in mathematics education, as it underpins students’ ability to develop logical reasoning and proportional thinking skills critical for advanced mathematical understanding. Despite its importance, students often struggle with these concepts due to the lack of learning activities that meaningfully connect mathematics to real-life contexts and cultural relevance. This disconnect highlights a gap in instructional approaches that fail to bridge abstract mathematical content with students’ lived experiences. Addressing this issue, the present study introduces a novel integration of the Pendidikan Matematika Realistik Indonesia (PMRI) approach with local cultural context, specifically the traditional Sumatran dish, namely lemang, to enhance students' conceptual grasp of ratio and proportion. The study aims to design and implement a PMRI-based learning sequence centered on the lemang context to facilitate meaningful learning experiences among junior high school students. Employing a design research methodology, the study involved seventh-grade students at SMP IT An-Nida Lubuklinggau, with data collected through student activity sheets (SAS), classroom observations, interviews, and documentation. Findings indicate that the integration of PMRI with the lemang context significantly supports students' progressive understanding of ratio and proportion, fostering both cognitive engagement and cultural appreciation. This research contributes to the enrichment of mathematics education by demonstrating how culturally contextualized PMRI designs can promote deeper learning and affirm the relevance of mathematical knowledge in students' everyday lives.